Simple and complex information processing speed in psychiatric samples - Jurkuvėnas, Vytautas; Bagdonas, Albinas; Germanavičius, Arūnas (Psichologija, 2016)
General information processing speed (IPS) impairment is a feature of many clinical conditions. Biological underpinnings of this impairment are being explored extensively. However, less attention has been paid to the fact that simple and complex IPS impairment might be analysed separately. The overall purpose of this paper was to analyse the role of simple and complex IPS in mental disorders. Three clinical groups were compared to healthy controls (N = 381): persons with self-reported history of mental disorder (N = 33), persons being treated for mild-moderate (F10-F99, except F20-F29) mental disorder (N = 35), and persons who were being treated for severe (F20-F29) mental disorder (N = 33). Neuropsychological battery of eleven computer administered tasks was used in order to measure simple IPS, complex IPS, memory, and set-shifting. Additionally, health-related and demographic information was collected. Participants in clinical groups reported poorer health on all measured variables, especially the group of persons who were being treated for severe mental disorder. ANOVA tests indicated that there were significant differences between compared groups on all cognitive domains. These differences were most pronounced in simple and complex IPS domains. Evidence is also provided that these differences are not due to demographic features of the sample, or even inter-correlations with memory and set-shifting abilities. Furthermore, a pattern of proportions of clinically significant cognitive deficits in mixed clinical sample (N = 101) versus control group of simple IPS and complex IPS suggests that measuring these cognitive domains might be beneficial both in research and in clinical practice.